Antinuclear Antibody Positivity in Patients With Hair Loss After COVID-19 Infection - Manav, Vildan; Erdil, Duygu; Koku Aksu, Ayşe Esra (Dermatology Practical & Conceptual, 2023)
Introduction: Hair loss is one of the most common disorders after coronavirus disease 2019 (COVID-19) infection. This study aimed to investigate the relationship between COVID-19-related hair loss and antinuclear antibody (ANA) positivity and patterns.Methods: ANA positivity and patterns were analyzed in 30 female COVID-19 patients with hair loss complaints and compared in terms of the presence of autoimmunity between patients with and without COVID-19 exhibiting hair loss.Results: ANA positivity and cytoplasmic patterns were detected in 40% of the patients with COVID-19 infection and hair loss. Trichodynia and diffuse hair loss were observed in 63.3% and 53.3%, respectively.Conclusions: In patients with COVID-19-related hair loss, diffuse hair loss and ANA positivity may be related to the high antibody levels triggered by COVID-19 infection.